Callus Induction In Leucaena (Leucaena leucocephala (Lam.) de Wit) As An Effort To Provide Target Transformation Through Agrobacterium tumefaciens - Ni Nyoman Nila Arieswari; Ida Ayu Astarini; Junita Hardini; Austin Ryan Garrido; Debora Margareth; Jennifer Crismonika; Sebastian S. Cocioba (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University, 2022)
Leucaena is a plant that produces biomass productivity in the form of hardwood for fuel with low humidity and high calorific value. However, Leucaena is also classified as an invasive plant which can cause the urgency of native plant species and ecosystems in Indonesia. Therefore, the formation of sterile Leucaena needs to be done, one of which is through genetic transformation using Agrobacterium tumefaciens. Callus is used as a target for transformants in the genetic transformation process, so it is necessary to use appropriate media and PGR. This study aimed to determine the type of media and the concentration of 2,4-D on callus induction. This research is an experimental study with a completely randomized design (CRD) method with two factors. The first factor is the type of media (MS and WPM) and the second factor is the concentration of 2,4-D (0; 0.25; 0.50; 0.75; 1.00; 1.25 and 1.50 mgL-1 ). Each treatment was repeated three times so that 42 experimental units were obtained. Parameters observed were callus initiation, callus fresh weight (gram), callus texture and color. Quantitative data is analyzed by analysis of variance (ANOVA). The results showed that the use of media had a significant effect (P<0.05) on callus fresh weight. The use of 2,4- D concentration had a significant effect (P>0.05) on callus texture. The use of WPM media resulted in the fastest callus emergence time (6.67±0.57), the best callus texture (crumb callus type 2) and the best callus color (green). Meanwhile, the highest fresh weight (2,48±0.83) was in the use of MS media. The fastest callus emergence time occurred in the control (without the addition of 2,4-D) (7.33±0.57 and 6.67±0.57), the highest average fresh callus weight (2,48±0.83 and 2.35±0.32) occurred in the treatment with the addition of 1.00 mgL-1 2,4-D with a crumb callus texture of type 2 and callus green color only appeared in the treatment with a concentration of 0.25 mgL-1.